Queer Theory and Sociology: Locating the Subject and the Self in Sexuality Studies - Isaiah Green, Adam (Sociological Theory, 2007)
In this paper, I revisit the relationship of queer theory and sociology in order to address some critical issues around conceiving the subject and the self in sexualities research. I suggest that while sociology and queer theory are not reducible to each other, sociology has its own deconstructionist impulse built into pragmatist and symbolic interactionist analyses of identity and subjectivity that is often overlooked by or reinvented through queer theory. But, conversely, queer theory has a very specific deconstructionist raison d'etre with regard to conceiving the sexual subject that marks its key departure from Foucault and sociology more generally. This deconstructionist mandate, by definition, moves queer theory away from the analysis of self and subject position—including those accruing from race, class and gender—and toward a conception of the self radically disarticulated from the social. This “anti-identitarian” position has been a source of criticism among some sociologists who find in queer theory an indefensible “refusal to name a subject” ( Seidman 1993:132). But this criticism, I suggest, stems from a misplaced effort to synthesize queer theory and sociology when, in fact, the two approaches to the subject are founded on incommensurable methodological and epistemological principles. Rather, I argue that the very promise of queer theory rests in a strong deconstructionism that exists in tension with, rather than as an extension of, sociological approaches to the self
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; méthodologie; premier cycle; périodes historiques; queer; sciences humaines; soc2014; sociologie; thématiques